the Indonesian Undergraduate TEFL Students' Experiences with “Replika; My AI Friend” As a Media In Learning Speaking - Anisah, Kania (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This is a new author guidelines and article/manuscript template of EXCELLENCE Journal of English and English Education – published by English Education Study Program since year 2021 publication. Article should be started by Title of Article followed by Authors Name and Affiliation Address and abstract. This abstract section should be typed in font size of 10 pt and number of words of 150-200. Special for the abstract section, please use normal margin. The single spacing should be used between lines in this article. If article is written in Indonesian, the abstract should be typed in Indonesian and English (Italic). If article is written in English, the abstract should be typed in English and Indonesian (Italic). The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format.